Caveolae: Formation, dynamics, and function. (August 2020) - Parton, Robert G.; McMahon, Kerrie-Ann; Wu, Yeping
Abstract: Caveolae are abundant surface pits formed by the assembly of cytoplasmic proteins on a platform generated by caveolin integral membrane proteins and membrane lipids. This membranous assembly can bud off into the cell or can be disassembled releasing the cavin proteins into the cytosol. Disassembly can be triggered by increased membrane tension, or by stress stimuli, such as UV. Here, we discuss recent mechanistic studies showing how caveolae are formed and how their unique properties allow them to function as multifunctional protective and signaling structures.